Troyer citrange growth inoculated with mycorrhizal fungus, in two growing media - Souza, Paulo Vitor Dutra de; Berjon, Manuel Abad; Orenga, Vicente Almela; Frofría, Manuel Agustí (Pesquisa Agropecuaria Brasileira, 1997)
The objective of the present study was to evaluate the effects of two substrate mixtures and arbuscular mycorrhyzae (AM) on the vegetative growth of Troyer citrange. Troyer citrange seeds, inoculated or not with G. intraradices Schenck & Smith were sown in plastic trays containing a substrate mixture of silica sand plus perlite plus Sphagnum peat (3:2:1; v/v/v). Sixty days after sowing the seedlings were transferred to black polyethylene bags containing either the sowing substrate or sedge black peat plus Sphagnum peat (1:1; v/v). AM increased vegetative growth of Troyer citrange independently of the growing media. The differences in vegetative growth between mycorrhyzal and nonmycorrhyzal seedlings were greater when cultivated in sedge black peat plus Sphagnum peat, which is an indication that this mixture, although with high levels of organic matter does not inhibit AM. Moreover, this treatment resulted in bigger trunk diameter of the seedlings that possibly could have positive effects on the anticipation of grafting time.